Optimalisasi Strategi Digital Marketing Berbasis Meta ads Terhadap Peningkatan Penjualan UMKM di Kota Palu - Andhyka Andhyka; Lisa Anggraini; Jenita Frisilia; Glen Willy Tatengkeng; Moh Reza Fajar Satrio (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This study aims to optimize Meta ads-based digital marketing strategies to increase sales of Micro, Small, and Medium Enterprises (MSMEs) in Palu City, which is characterized by low digital literacy among MSMEs, but 70% of its residents are active social media users. This study used a quantitative approach with a quasi-experimental design involving 50 MSMEs, who were divided into two groups: an experimental group (Meta ads mentoring) and a control group (independent use of Meta ads). The results showed that the Meta ads strategy with regular mentoring significantly increased MSME revenue compared to the independent strategy. Key success factors included the relevance of ad content, precise audience targeting, and campaign performance data analysis. These findings can be a reference for businesses and local governments in designing evidence-based digital marketing mentoring programs.